Digital era sharing leadership era: Evidence of waqf ecosystem activities on campus of Universitas Islam Bunga Bangsa Cirebon - Kori Vidiyati; Sukirno; Aslam; Its Selasi; Ahmed Munazim; Heru Kahyono (Journal of Islamic, Social, Economics and Development, 2024)
This paper describes the leadership of small-scale sharing on campus in the Community Service Lecture (KPM) of Universitas Islam Bunga Bangsa Cirebon (UIBBC), where the KPM chairman who can delegate team members is also an agent of student waqf reform by implementing professional/service waqf. With a qualitative approach, data collection from field studies and interviews as primary data supplemented by secondary data from journal articles related to the subject. It was found that the emergence of design-thinking of student leaders in the digital era proves the sharpness of creativity by paying attention to HR skills; sharing leadership causes the output of task delegation to be maximized; BWI Leadership messages reach students. The novelty of the conversation of professional / service waqf which KPM UIBBC students directly carry out as one of the waqf literacy for the community. Direct implications for maukuf ‘alaih, namely the around community and wakif's spiritualism, are increased.